Rethinking Business Models in the Great Depression: The Failure of America's Vacuum Cleaner Industry. Issue 2 (2019) - Scott, Peter
Abstract : We examine the factors leading to the onset of organizational rigidities in the dominant vacuum cleaner firms of the 1920s, Hoover and Eureka. Strategies aimed at strengthening organizational commitment, in conjunction with low levels of organizational diversity—owing to managerial hierarchies dominated by men recruited from the sales force—restricted organizational flexibility and adaptability while accentuating resistance to change. In conjunction with core competencies that largely reflected conditions in the previous rapid-growth phases of both firms, organization rigidity left them vulnerable to the new conditions of the Depression, including product and value chain innovation by a new entrant, Electrolux.